Estrategias metodológicas para la enseñanza del estilo pecho, en la natación, en el sexto año de educación general básica, de la escuela fiscal mixta Dr. Isidro Ayora, del cantón Latacunga en el año lectivo 2013-2014 - Hernández Villalobos, Angélica Alexandra (2015)
Swimming has been for a long time one of the most attractive disciplines and it is the way that allows students to develop in a 80% abilities, skills, basic motor skills and reach the fullest potential where comprehensive development of students is achieved, characterizing as the relevant active source for the personal improvement, sporting and integral of people. Using a program of methodological strategies allows that the professional of physical education greatly improve the teaching - learning process to the point of leaving indelible mark on students and create meaningful learning. In the case of this program is that there is no other developed and for the aesthetics of breaststroke captures the interest of the athlete with the learning of a new style and little practiced….